2012
DOI: 10.5796/electrochemistry.80.749
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Performance of All-Solid-State Battery Using a Lithium Superionic Conductor Li10GeP2S12

Abstract: A solid electrolyte, Li 10 GeP 2 S 12 , exhibits a high lithium ionic conductivity of 12 mS/cm at room temperature. Because of its high ionic conductivity, high charge-discharge performance would be expected for the all-solid-state batteries using the Li 10 GeP 2 S 12 electrolytes. In this study, all-solid-state batteries using Li 10 GeP 2 S 12 , were constructed and their battery performances were examined. The batteries using the Li 10 GeP 2 S 12 electrolyte showed higher discharge capacities than those with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(74 citation statements)
references
References 6 publications
0
70
0
3
Order By: Relevance
“…The ionic conductivity of LSiPSO was 3.2 × 10 −4 S cm −1 at room temperature. This value is one order of magnitude smaller than that of LGPS, which shows the ionic conductivity of 1.2 × 10 −2 S cm −1 for a sintered pellet (Kamaya et al, 2011) or 6-8 × 10 −3 S cm −1 for a cold-pressed pellet (Kato et al, 2012;Shin et al, 2014;Han et al, 2015). Nevertheless, the ionic conductivity value of LSiPSO meets the conductivity criterion (>10 −4 S cm −1 ) proposed for practical electrolytes in lithium batteries (Goodenough and Kim, 2010).…”
Section: Ionic Conductivitymentioning
confidence: 65%
See 1 more Smart Citation
“…The ionic conductivity of LSiPSO was 3.2 × 10 −4 S cm −1 at room temperature. This value is one order of magnitude smaller than that of LGPS, which shows the ionic conductivity of 1.2 × 10 −2 S cm −1 for a sintered pellet (Kamaya et al, 2011) or 6-8 × 10 −3 S cm −1 for a cold-pressed pellet (Kato et al, 2012;Shin et al, 2014;Han et al, 2015). Nevertheless, the ionic conductivity value of LSiPSO meets the conductivity criterion (>10 −4 S cm −1 ) proposed for practical electrolytes in lithium batteries (Goodenough and Kim, 2010).…”
Section: Ionic Conductivitymentioning
confidence: 65%
“…So far, a number of studies motivated by this attractive feature of LGPS have investigated the charge/discharge performances of all-solid-state cells based on LGPS and have suggested that developing other LGPS-type solid electrolytes would be a significant step toward the realization of all-solid-state batteries with higher power and energy densities (Kato et al, 2012(Kato et al, , 2016. However, the following two obstacles need to be overcome before LGPS finds wide application as a solid electrolyte in batteries: the fact that it contains germanium, which is relatively rare and hence expensive, and its low electrochemical stability when in contact with lithium metal.…”
mentioning
confidence: 99%
“…有机-无机杂化体系一般指在 PEO 基体中加入无机 填料的复合电解质体系, 此体系的导电率一般在 10 -6 ~ 10 -5 S/cm [20,21] . 无机填料加入电解质中, 主要起到两方 面的作用: (1)打乱基体中聚合物链的秩序, 降低结晶度; Figure 5 The test mould for all-solid-state battery with inorganic electrolyte [60] 2011 年, 日本东京工业大学研究人员 [44] Figure 6 Charging/discharging curves and cycle performance of LiCoO 2 /Li 10 GeP 2 S 12 /In cells [44] 2012 年, 日本丰田汽车公司 [61] …”
unclassified
“…Low conductivity (10 -4~1 0 -3 S/cm), high grain boundary resistance and high calcination temperature of these oxide solid electrolytes cause increased volatility, phase transition and impurity, decreasing the total quality of Li ion battery. On the other hand, sulfide-based solid electrolyte including Li10GeP2S12 (LGPS) display high conductivity almost similar to that of liquid electrolytes 31 . However, it is smelly, expensive, unstable under air and reactive with water generating harmful H2S.…”
Section: Introductionmentioning
confidence: 99%